ANALISIS KELAYAKAN INSTALASI LISTRIK PADA GEDUNG PT. HONDA SEMOGA JAYA PRIMA - Zainal, Muhammad Isradi; Pongky, Patunru; Yoga, Yoga (Program Studi Kesehatan dan Keselamatan Kerja, 2021)
The quality of electrical installations is highly dependent on the implementation and application of standard electrical installation regulations, namely PUIL in 2011 and other regulations of Law number 30 of 2009 concerning supporting electricity. Electrical installations including safety, protection, and equipment must be properly maintained. Due to the age factor, the installation will experience wear, aging or damage that will interfere with the installation. Therefore, the installation must be periodically checked and repaired parts that are worn, damaged or aging must be replaced. This type of research uses a qualitative descriptive method. Based on the results of this study, there is a feasibility of installation in the PT. Honda Hopefully Jaya Prima Balikpapan, 46.6% were declared eligible and 53.3% were declared ineligible. Electrical installations in terms of installation equipment, there are 46.6% of the 15 installations that meet the 2011 PUIL eligibility standards, while from the electrical installation safety there are 80% of the 15 installations that meet the 2011 PUIL eligibility standards. % of 15 installations that meet the 2011 PUIL eligibility standards. Installations in terms of insulation resistance meet 100% of the 15 feasibility installations mentioned in the 2011 PUIL standards. Judging from the grounding or grounding resistance, there are 93.3% of the 15 installations that are declared eligible according to with PUIL 2011. Keywords: Feasibility of electrical installation, PUIL 2011